Strata data. (Superstream series (O'Reilly (Firm)), 2021)
Businesses in every industry strive to turn data into optimal decisions—a challenge that’s grown even more complex in these uncertain times. So how can organizations better translate their data into actionable insights? The ability to quickly collect, analyze, and visualize your data to make data-driven business decisions is imperative to building an effective data strategy. And we can now do business analytics that reflect your data in near real time. But are you taking advantage of those capabilities? Join us to learn more about the latest trends in data that are powering growth, increasing efficiency, and optimizing business decisions. About the Strata Data Superstream Series: This recording of a four-part series of half-day online events gives viewers an overarching perspective of key topics that will help your organization maximize the business impact of your data.